2000
DOI: 10.1159/000016019
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of <sup>99m</sup>Tc-HMPAO-SPECT for Neurological Outcome/Recovery at the Acute Stage of Stroke

Abstract: Background and Purpose: Combined perfusion and oxygen metabolism PET imaging is highly predictive of spontaneous outcome after middle cerebral artery (MCA) stroke, independent of clinical scores, but whether the assessment of perfusion alone by SPECT provides similar information remains unclear. We have assessed the prognostic value of 99mTc-HMPAO-SPECT at the acute stage of stroke. Methods: Twenty-seven first-ever nonhemorrhagic MCA territory stroke patients were prospectively studied 4–20 h (mean:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, even in the same clinical subgroup, we observed a wide spectrum of outcomes. Indeed, it is known from daily clinical practice and from recent single-photon emission CT studies 27 that patients presenting with the same symptoms may subtend diverse etiologies and perfusional deficits. This variability, which remains unrevealed in Bamford's classification, may explain the different therapeutic response and the clinically relevant frequency of intracranial hemorrhage after thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the same clinical subgroup, we observed a wide spectrum of outcomes. Indeed, it is known from daily clinical practice and from recent single-photon emission CT studies 27 that patients presenting with the same symptoms may subtend diverse etiologies and perfusional deficits. This variability, which remains unrevealed in Bamford's classification, may explain the different therapeutic response and the clinically relevant frequency of intracranial hemorrhage after thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that patients with a normal SPECT scan, performed within 3–6 h from stroke onset, will most likely recover spontaneously and therefore may not benefit from thrombolysis [50,51,52]. Furthermore, studies performed at a later time after the onset of symptoms could also identify different tissue compartments and SPECT results could help predict neurological development in addition to neurological scores [53, 54]. …”
Section: Single-photon-emission Computed Tomographymentioning
confidence: 99%
“…[12] Several studies have highlighted the validity of HMPAO-SPET as a prognostic tool in ischaemic stroke by showing a correlation between the size and=or the degree of hypoperfusion and neurological and functional outcome. [13][14][15] However, apart from assessing and visualizing CBF, SPET does not provide any information on the metabolic state of brain, thus limiting its use in the evaluation of the pathophysiology and outcome of the ischaemic penumbra. Moreover, the occurrence of spontaneous reperfusion of necrotic tissue in the first 48 hours after stroke prevents SPET from distinguishing tissue still at risk of infarction from already infarcted brain areas.…”
Section: Single-photon Emission Tomographymentioning
confidence: 99%